Distribution of Poverty in West Kalimantan - Ummi Rahimah (Badan Pusat Statistik Provinsi Kalimantan Barat, 2023)
Poverty in each region is caused by various factors. Therefore, the initial step in overcoming it can be grouping regions based on their characteristics. In this study, an analysis was carried out using all provinces in Indonesia and after that, the urban districts in West Kalimantan province were grouped with urban districts from other provinces in cluster 1. The indicators used in this study were the percentage of poor people, poverty severity index, depth index poverty, human development index, expected length of schooling, average length of schooling, and adjusted per capita expenditure. This study uses k-means clustering analysis. The results of phase 1 research obtained 3 clusters of poverty levels, namely cluster 1 is a medium poverty rate of 26 provinces, cluster 2 is a high poverty rate of 5 provinces, and cluster 3 is a low poverty rate of 5 provinces. The results of phase 3 research obtained 3 clusters of poverty levels, namely Cluster 1 is a moderate poverty rate of 65 urban regencies, cluster 2 is a high poverty rate of 103 urban regencies, and Cluster 3 is a low poverty rate of 224 urban regencies.